Research note: The distributional impact of local social benefits in Croatia - Martina Pezer; Slavko Bezeredi; Chrysa Leventi (University of Essex, Institute for Social and Economic Research (ISER), 2018)
The aim of this research note is to analyse the distributional impact of five types of local social benefits (compensation for housing costs, old-age income supplement, grant for a newborn child, kindergarten subsidy and city transport subsidy) in the four major Croatian cities - Zagreb, Split, Rijeka and Osijek - which is a first analysis of this kind for Croatia. Using miCROmod - the Croatian tax-benefit microsimulation model, a comparative analysis of benefits and their generosity has been conducted; their income redistribution and poverty reduction effects have also been investigated. Results reveal that, in all local benefit systems considered, the most significant resources are devoted to the city transport subsidy and the kindergarten subsidy. If we compare the per capita values, the most generous benefits are found in Zagreb, followed by Rijeka, Osijek and Split. Also, social protection benefits of Zagreb and Rijeka are the most redistributive, achieving the highest poverty headcount reduction.
Keywords: D31; H70; I38; 330; miCROmod; local self-government; social protection benefits; Croatia; poverty